Synergistic effect of PARP inhibitor and BRD4 inhibitor in multiple models of ovarian cancer. Issue 5 (8th February 2023) - Huang, Yuhan; Liu, Chen; You, Lixin; Li, Xi; Chen, Gang; Fan, Junpeng
Abstract: Ovarian cancer has the highest facility rate among gynaecological tumours. Current therapies including PARP inhibitors have a defect that ovarian tumour is easy to recurrent and become resistant to therapy. To solve this problem, we found that BRD4 inhibitor AZD5153 and PARP inhibitor olaparib had a widespread synergistic effect in multiple models with different gene backgrounds. AZD5153 sensitizes cells to olaparib and reverses the acquired resistance by down‐regulating PTEN expression levels to destabilize hereditary materials. In this study, we used the following multiple ovarian cancer models PDX, PDO and 3D/2D cell lines to elucidate the co‐effect of AZD5153 and olaparib in vivo and in vitro. The similar results of these models further proved that the mechanism identified was consistent with the biological process occurring in ovarian cancer patients after drug treatment. This consistency between the results of different models suggests the possibility of translating these laboratory research findings into clinical studies towards developing treatments.